ANALYTICAL QUANTIFICATION OF BOSUTINIB IN NANOCARRIER USING UV AND HPLC: METHOD DEVELOPMENT AND VALIDATION - AGADE, RISHABH; HUSSAIN, UJBAN; TRIVEDI, SAGAR; BELGAMWAR, VEENA (International Journal of Applied Pharmaceutics, 2024)
Objective: Bosutinib, a potent tyrosine kinase inhibitor, holds significant promise in cancer therapy, particularly in Breast Cancer treatment. This study focuses on the analytical quantification of Bosutinib in Nanocarriers (BNCs) essential for quantification in terms of targeted delivery. Methods: A comprehensive method development and validation process was undertaken utilizing UV-visible spectroscopy and High-Performance Liquid Chromatography (HPLC). Preformulation studies confirmed the purity and physicochemical properties of bosutinib. UV-visible spectroscopy established a calibration curve for bosutinib and BNCs, with precision, accuracy, Limits of Detection (LOD), and Limits of Quantification (LOQ) determined. HPLC analysis further validated bosutinib quantification, ensuring the robustness and reliability of the analytical method. Results: Bosutinib and BNCs were evaluated using UV-visible spectroscopy, revealing λ max at 263 nm and 277 nm, respectively, showing a strong correlation with the regression coefficient (R2) being 0.9969 and 0.9994, respectively. The precision (intra-day and inter-day) data shows strong reproducibility with a Percentage Relative Standard Deviation (%RSD) of less than 1.5%. Completely distinguished sharp peaks of bosutinib and BNCs were developed using HPLC under ambient settings; 3.974±0.006 and 3.083±0.004 was the Resolution Time (Rt) at which bosutinib and BNCs were discovered, respectively. The Theoretical Plate (TP) values of 5179±93 and 2598±85 and the Tailing Factor (TF) of1.00±0.002 and 1.10±0.004 were both within the predetermined bounds. Conclusion: The developed UV and HPLC methods offer accurate and reliable quantification of bosutinib in a nanocarrier, essential for optimizing drug delivery strategies and therapeutic outcomes in cancer treatment. This analytical approach contributes to advancing pharmaceutical research in precision medicine and targeted drug delivery systems.